Anthocyanin and Phenolic Acids Contents Influence the Color Stability and Antioxidant Capacity of Wine Treated With Mannoprotein - Yue, Xiao-feng; Jing, Si-si; Ni, Xiao-fan; Zhang, Ke-kun; Fang, Yu-lin; Zhang, Zhen-wen; Ju, Yan-lun (Frontiers in Nutrition, 2021)
Wine is consumed by humans worldwide, but the functional components are lost and the color changes during its production. Here, we studied the effects of mannoprotein (MP) addition (0 g/L, 0.1 g/L, and 0.3 g/L) upon crushing and storage. We measured anthocyanins, phenolic acids profiles, color characteristics, and antioxidant activities of wine. The results showed that the addition of MP before fermentation significantly increased the total phenolic content (TPC), total anthocyanin content, total tannin content (TTC), total flavonoid content, and total flavanol content in wine, whereas the addition of MP during storage had the opposite effect. The addition of MP before alcohol fermentation significantly increased the amount of individual anthocyanins and individual phenolic acids, maintained the color, and increased the antioxidant capacity of wine. In addition, the addition of 0.3 g/L MP during storage increased the content of individual phenolic acids and TPC of wine. However, the addition of 0.1 g/L MP during storage significantly reduced the TPC, TAC, TTC and individual anthocyanin content (except for malvidin-3-glucoside and malvidin-3-acetly-glucoside); meanwhile, the treatment attenuated the color stability and antioxidant capacity of wine. The results demonstrated that the addition of MP before alcohol fermentation could increase the functional components and improve the color stability and antioxidant capacity of wine.